Особливості маркетингу у сфері освітніх послуг - Болотна, О. В. (НДІ ПЗІР НАПрН України, 2021)
Наукова робота присвячена дослідженню маркетингу у сфері послуг. Автор проаналізував проблеми ринку на рівні держави та мікрорівні вищих навчальних закладів. Надані рекомендації щодо більш глибокого сприянню роботи маркетингових служб вищих навчальних закладів, щодо аналізувати потреб споживачів та підвищення конкурентоспроможності організації, однак при цьому необхідно враховувати роль держави, яка встановлює переліки професій і спеціальностей, за якими ведеться освіта та формує базовий асортимент освітніх послуг. // Scientific work is devoted to the study of marketing in the service sector. The author analyzed the market problems at the state level and micro level of higher educational establishments. Recommendations are provided for a deeper assistance to the work of marketing services of higher educational establishments, to analyze the needs of consumers and raising the competitiveness of the organization, but it is necessary to take into account the role of the state that establishes the listings of professions and specialties that are educated and forms a basic assortment of educational services.
Keywords: маркетинг; освітні послуги; marketing; educational services